2007
DOI: 10.1002/ptr.2288
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of Devil's Claw tablets in patients with general rheumatic disorders

Abstract: Arthritis and other rheumatic conditions (AORC) are the leading cause of disability, are associated with poor quality of life and incur considerable direct and indirect costs. It is considered that the instance of AORC will continue to increase. To assess the effectiveness, safety and tolerability of Harpagophytum (Bioforce) in the treatment of AORC, a single group open study of 8 weeks duration (259 patients) was performed in the United Kingdom. Effectiveness was assessed by numeric rating scales, the Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 19 publications
(18 reference statements)
1
16
0
3
Order By: Relevance
“…Subsequently, a single group open study was performed on 259 patients administered with devil's claw dry extract (960 mg/day) for 8 weeks. The authors reported a significant reduction in global pain and stiffness alongside with significant improvements in function and mean pain scores for hand, wrist, elbow, shoulder, hip, knee, and back pain (Warnock, McBean, Suter, Tan, & Whittaker, ). The efficacy of devil's claw was demonstrated in a rat model of arthritis, as well (Andersen, Santos, SeabraMde, da Silva, & Tufik, ).…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Subsequently, a single group open study was performed on 259 patients administered with devil's claw dry extract (960 mg/day) for 8 weeks. The authors reported a significant reduction in global pain and stiffness alongside with significant improvements in function and mean pain scores for hand, wrist, elbow, shoulder, hip, knee, and back pain (Warnock, McBean, Suter, Tan, & Whittaker, ). The efficacy of devil's claw was demonstrated in a rat model of arthritis, as well (Andersen, Santos, SeabraMde, da Silva, & Tufik, ).…”
Section: Experimental Studiesmentioning
confidence: 99%
“…The patients with more severe pain tended to use more Tramadol s but not to the maximum permitted dose (Chrubasik et al, 1999). Warnock et al (2007) conducted a single group, open, 8-wk clinical study in the United Kingdom on 259 patients suffering from arthritis and other rheumatic conditions (AORC) where pain (rated 2-7 out of 10) was present at least 2 days per week in the affected area during the previous 8 weeks. A. Vogel Rheuma Tabletten s containing 480 mg of H. procumbens dried extract each was selfadministered every morning and evening (960 mg/d) with meals and the effectiveness assessed for 207 patients.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…contributing to the prevention of malignant transformation in a 761 similar fashion to that noted by resveratrol (Cho et al, 2012;Bamba 762 et al, 2011;Choi et al, 2008). (Grant et al, 2007;Warnock et al, 2007;Romiti et al, 2009). Unger 804 and Frank (2004) are also associating herbal supplements or vegetal rich diets nitric oxide production on whole-blood assay.…”
mentioning
confidence: 70%